Acoustic behaviour of textile structures. Issue 1 (10th December 2021) - Paul, Parikshit; Mishra, Rajesh; Behera, B. K.
Abstract: Recent history has witnessed substantial growth in public concern related to noise pollution due to industrial progress. As much as this situation imposes a burden on textile producers, it also opens a new battlefield against conventional acoustic materials, where textiles can prevail. Conventional acoustic materials are in the line of fire due to their adverse effects on the ecosystem as well as on human health. This situation can offer a business advantage to textile producers, provided that the damage inflicted on the environment throughout the whole life cycle of the textile product is minimised and the functional properties are improved. A lot of research has been done about textiles for controlling noise pollution in the last forty years; there is still a lack of a systematic and holistic approach to those investigations. The challenge lies in attaining desired sound levels while simultaneously maintaining or enhancing the audio environment. A scientific approach to develop textile based acoustic materials/structures is deeply desired. Desirable features of acoustic materials in terms of ecology and economy must be explored, such as recyclability, light weight, and cost effectiveness. Design is a challenging task because varying material types together with acoustic textiles can be used simultaneously in different shapes, thicknesses, sequences, perforation, and groove properties. As the sound absorbers are composed of multiple layers of different materials, accurate modelling of the acoustical behaviour is often difficult. We also need systematic findings in acoustic performance of unidirectional textile structures, woven two-dimensional structures, nonwoven structures and stacked structures. There are unexplored areas in the study of suitable three-dimensional woven structures, whether orthogonal, angle interlock or honeycomb structure, and evaluation of their acoustic performance. The combination and sequence of different textile structures need to be ascertained for achieving the required acoustic performance. The studies on 3D spacer fabrics for acoustic insulation are still in the initial phase and therefore the emphasis in all these studies is primarily to understand the role of the face and back layer's density, air permeability through the spacer structure and thickness of the spacer fabric.